Value Engineering Practices in Indonesia: A Systematic Literature Review (Architecture Image Studies, 2025)
This study systematically reviews the development and implementation of value engineering (VE) practices in Indonesia to identify research trends, methodological approaches, and key thematic areas. Using the PRISMA framework, 18 relevant studies were retrieved from the Scopus and Google Scholar databases. The findings reveal that VE research in Indonesia remains fragmented, with limited integration between academic studies and industry applications. Most publications focus on construction and infrastructure sectors, emphasizing cost optimization rather than holistic value creation. Methodologically, case studies dominate, while quantitative and decision-support approaches are underrepresented. The review highlights challenges such as the lack of standardized procedures, institutional support, and awareness of VE benefits among practitioners. Strengthening interdisciplinary collaboration, policy support, and methodological diversity is essential to advance VE implementation and research impact in Indonesia.